THE EFFECT OF GREEN HUMAN CAPITAL ON EMPLOYEE PERFORMANCE WITH GREEN STRUCTURAL AS A MODERATING VARIABLE - Mulyadi, Mulyadi; Sudianto, Sudianto; Amang, Andi; Dewi, Susantriana; Djunaedi, Djunaedi (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract The aim of this research is to analyze the influence of green human capital on employee performance with Green Structural as moderation. The population in this study were company employees. The sampling technique in this research was purposive sampling technique. The collected data was analyzed using smartPLS. The results of this research show that green human capital has a positive effect on employee performance . Green structural is able to moderate green human capital towards employee performance. Keywords: Employee Performance, Green Human Capital, Green Structural